The Propagation of Weapons of Mass Instruction Outside the Hegemonic World of Education - Burgoyne, John (Proceedings of the International Conference on Networked Learning, 2004)
It is beyond doubt or the need for further investigation or evidence that the means to deploy networked, blended and e-leaning in much less than 45 minutes to affect large populations, well beyond the traditional battlefield of face to face learning, exist on a large scale, and mainly outside the traditional institutional domains of higher and other forms of education.